Implementation of Adaptive Methods in Individualized Learning for Early Childhood Students with Intellectual Disabilities: A Case Study - Dava Damara, Septian; Aditya Hidayah , Muhamad; Ratriani, Sintia; Dwi Mu'azzizah, Martha; Farel Al fawazi, Muhammad (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Children with intellectual disabilities require specialized educational approaches that accommodate their unique learning needs. Adaptive individualized learning has become an essential strategy in special education, particularly at the early childhood level, to support cognitive, social, and motor development. SLBN Keleyan in Socah, Bangkalan, has been recognized for its efforts in implementing such approaches despite various limitations. Aims and scope of paper: This study aims to examine the types of adaptive individualized learning implemented for early childhood students with intellectual disabilities at SLBN Keleyan, Socah. The primary focus is on the application of special education approaches that address individual needs and the roles played by teachers, the school principal, and the school environment in creating meaningful learning experiences. Methods: This research employed qualitative methods, including direct observation, semi-structured interviews, and document analysis. Data were collected from teachers, the school principal, and supporting documentation within the school environment. Results: The findings indicate that SLBN Keleyan implements individualized learning strategies through the use of visual aids, educational games, and simple motor activities. The principal plays a pivotal role in fostering collaboration between the school, parents, and therapists to ensure cohesive support for each student. Despite challenges such as limited facilities, the learning process remains effective. Contribution: This study underscores the importance of adaptive individualized learning in the education of children with special needs. It also reinforces previous findings (Fakhiratunnisa & Desiningrum, 2022; Harsiwi & Wulandary, 2024) that identify SLBN Keleyan as a potential model for inclusive and adaptive special education practices in the Bangkalan region.